EFL Teachers’ Perceptions and Strategies in Fostering Learner Autonomy during the COVID-19 Pandemic - Khairani Putri Salsya; Lulu Laela Amalia (Basic and Applied Education Research Journal, 2022)
Learner autonomy is required when studying English as a Foreign Language (EFL). In fact, teacher-centered learning is still dominating the learning activity, where the students still depend on the teacher as the source of knowledge in the classroom, including in Indonesian context. Unfortunately, the world is now facing serious pandemic COVID-19 which has caused the teachers not able to do the teaching and learning process conventionally. This research sought two senior high school teachers in Lampung. In this study, questionnaires and semi-structured interviews were used as instruments. This qualitative research aimed to describe the EFL teachers’ perceptions and strategies to foster learners’ autonomy during the COVID-19 pandemic. Both EFL teachers agreed that autonomy meant that students could choose how they learned and be in charge of their own learning. The EFL teachers fostered learner autonomy by using some strategies such as assigning e-diaries, asking for a presentation based on certain tasks, and allowing students using educational apps as it is one of a tool to reach students’ learner autonomy. The result showed that teachers had positive perspectives and the eagerness to foster learner autonomy. Furthermore, the teachers’ strategies affect positive responses for their students during online learning due to the COVID-19 pandemic.